Hubungan Penggunaan Media Sosial dengan Kualitas Tidur Mahasiwa S1 Ilmu Keperawatan Semester 4 Universitas Islam Sultan Agung Semarang - Listianengsih Listianengsih; Nutrisia Nu’im Haiya; Iwan Ardian (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Background: social media has become in important part of students’ daily lives,however, excessive use, especially at night, can disrupt sleep patterns and lower sleep quality. Poor sleep quality affects students physical health, mental well-being, and academic performence. This study aims to determine the relationship between social media use and sleep quality among nursing students. Method: this study used a quantitarive method with a cross-sectonal approach. Data were collected using questionnaires from 121 respondents selected through the slovin formula ang analyzed using the chi-square test. Results: the findings showed that most respondents were active social media users ( 71.9%) and had poor sleep quality (70,2%), the chi-square test indicated a significant relationship between social media use and sleep quality, with a p-calue of 0,001 and r : 0,317. Conclusion: students who are more active in using social media tent to have poorer sleep quality. It is recommended that students limit social media use, especially at night, to maintain healthy sleep patterns and overall weell-being.